Women, whistleblowing, WikiLeaks - Avila, Renata, 1981-; Harrison, Sarah, 1981 or 1982-; Richter, Angela (OR Books, 2017)
"The most controversial activist organization of the 21st century, WikiLeaks has attracted strong, divergent opinions from across the political spectrum. Lauded by its supporters for its indispensable role in holding governments, corporations, and human rights abusers to account, its advocates and journalists have been excoriated by opponents as traitors, threats to legitimate governments, and misogynists. Yet so much media attention is focused upon founder Julian Assange, and his ongoing confinement in the Ecuadorian embassy in London, that the broader dimensions of WikiLeaks are rarely aired. Especially critical in these omissions is the role of women, both in the organization and the more general struggle for information freedom. Women, Whistleblowing, WikiLeaks presents a conversation between three extraordinary advocates who have been at the forefront of such activity: acclaimed journalist and human rights advocate Sarah Harrison, Croatian-German theater director, activist and author Angela Richter, and Renata Avila, a celebrated Guatemalan human rights lawyer and digital rights expert. Ranging widely, from the dishonesty of the mainstream media and its contrasting treatment of Edward Snowden and Chelsea Manning to the terrifying monopolization of personal data under tech behemoths such as Facebook and Google, this book is a crucial intervention in the ongoing debate around digital activism."